Pemanfaatan Artificial Intelligence dalam Pembelajaran Pendidikan Agama Islam - Fuad, A Jauhar; Mohd Fakhruddin, Fathiyah (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2024)
The use of Artificial Intelligence in Islamic religious education learning needs to pay attention to policies, innovations and their implications. This study uses a literature review by reviewing several journals and books published in 2018-2024. The findings in this study, first, the use of AI needs support from various parties in terms of policy, infrastructure, human resources, funding and the need for a human performance technology approach. Second, many applications are used in the use of AI including: Concordance-Based Word Search, Al-Quran index web application, Al-Quran translation question and answer application using the Query Expansion Method, Muslim Pro and ChatGPT applications. Third, there are positive and negative impacts of the use of AI, facilitating the learning process if accompanied by ethics and morals. The dependence of learning on technology and the validity of the information conveyed by AI in interpreting the Al-Quran and other sources.